Strategi Pengembangan Lahan Irigasi Rawa di Daerah Rawa Pasang Surut Belawang-Kalimantan Selatan - Elias Wijaya Panggabean; Bangkit Aditya Wiryawan (Balai Teknik Irigasi, 2016)
Swamp reclamation project that had been carried out by the Government of Indonesia in Sumatra and Kalimantan few decades ago was primarily aimed at strengthening national food security and transmigration project. However now, contribution of tidal swamp farming to national food security is still low. Instead, nowadays there are more irrigated swamp land that had been converted into oil palm or rubber plantations. Irrigated swamp field of Belawang (Barito Kuala Regent) is one of the area which had been widely converted to rubber plantations. Many factors lead to these phenomena. This study examined the key factors that led to land conversion and followed by formulating strategies to promote the role of irrigated swamp fields in supporting food security. The research was conducted in 2014 under quantitative approach and using SWOT analysis method. Data were obtained through in-depth interview towards key informants. This study suggested that the strategy for the development of irrigated tidal swamp in Belawang should be carried out by remapping the appropriate swamp type for food crops and plantations. Furthermore, planned commodity diversification is the answer for food security and local economic problems.